Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1016/j.jsps.2012.09.001
|View full text |Cite
|
Sign up to set email alerts
|

A study investigating the level of satisfaction with the health services provided by the Pharmacist at ENT hospital, Eastern Region Alahsah, Kingdom of Saudi Arabia

Abstract: The current study aims to evaluate the patient's level of satisfaction with health care services provided by the pharmacist at Aljaber ENT hospital, Eastern Region Alahsah, Kingdom of Saudi Arabia. A cross sectional study was planned from 1st March 2011 until 31st May 2011. A 27 item questionnaire was used, scoring of the responses was done to classify the patient satisfaction into sublevels. The maximum possible score was 36; those scoring less than twenty were graded as poor satisfaction level followed by mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
45
4
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 7 publications
9
45
4
4
Order By: Relevance
“…Adicionalmente, os farmacêuticos possuem conhecimento entre satisfatório/regular para a dispensação de medicamentos, e acreditam que precisam melhorar quanto às ações de cuidados ao paciente. Poucos são os estudos que verificam o nível de satisfação dos usuários em farmácias públi-cas de dispensação de medicamentos básicos e, de modo geral, estas pesquisas se concentram em farmácias comunitárias privadas e hospitalares 2,11,19 . Entretanto, é importante contribuir com o campo de investigação da satisfação nestas farmácias públicas, e neste nível de atenção à saúde em países em desenvolvimento.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Adicionalmente, os farmacêuticos possuem conhecimento entre satisfatório/regular para a dispensação de medicamentos, e acreditam que precisam melhorar quanto às ações de cuidados ao paciente. Poucos são os estudos que verificam o nível de satisfação dos usuários em farmácias públi-cas de dispensação de medicamentos básicos e, de modo geral, estas pesquisas se concentram em farmácias comunitárias privadas e hospitalares 2,11,19 . Entretanto, é importante contribuir com o campo de investigação da satisfação nestas farmácias públicas, e neste nível de atenção à saúde em países em desenvolvimento.…”
Section: Discussionunclassified
“…Deste modo, como não eram tidos como essenciais ao funcionamento dos serviços, os estudos de avaliação se desenvolveram vagarosamente e de forma fracionada 1 . No cenário atual, pesquisa sobre satisfação dos usuários tem sido considerada um importante indicador dos serviços de saúde, por meio do qual é possível acessar a qualidade e a aplicabilidade desses serviços 2 . Nesse contexto, os serviços de saúde podem ser avaliados de várias maneiras, tanto pela estrutura física e mão-de-obra humana e material, quanto às atividades realizadas com o intuito de fornecer melhoria terapêutica ao paciente e relações interpessoais.…”
Section: Introductionunclassified
“…Recent studies show that users become more satisfied with the services of a pharmacy when the pharmacist interacts with them and gives clear explanations about the medications (Al-Arifi, 2012;Alturki, Khan, 2013). Alturki and Khan (2013) found that 61.2% of users expressed dissatisfaction, as they did not understand the information provided by the pharmacist.…”
Section: Introductionmentioning
confidence: 99%
“…Alturki and Khan (2013) found that 61.2% of users expressed dissatisfaction, as they did not understand the information provided by the pharmacist. In addition, Catic, Jusufovic and Tabakovic (2013) showed that the features most appreciated by users about the pharmacist were the explanations and providing appropriate responses (79.1%), followed by consultation offered by these professionals who clearly informed the patient about the drugs proposed by the physician.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation